Ultrasonic degradation kinetics and rheological profiles of a food polysaccharide (konjac glucomannan) in water. (September 2017) - Li, Jing; Li, Bin; Geng, Ping; Song, Ang-Xin; Wu, Jian-Yong
Abstract: This study was carried out to evaluate the effects of power ultrasound (US) on the molecular weight and rheological properties of a food polysaccharide, konjac glucomannan (KGM). Upon the exposure of KGM solution (1% w/v in water) to US at a relatively high power intensity (50 W/cm 2 ), the apparent viscosity decreased rapidly from about 50 Pa s to a negligible level within 10–20 min. The intrinsic viscosity ([η]) of KGM solution decreased gradually during the US exposure with a time course closely fitted to the first-order polymer degradation kinetics (random chain scission). The US treatment also caused a significant reduction of particle size (Zavg ) of KGM aggregates and changes in the rheological properties including the decrease of storage modulus (G′) and loss modulus (G″), and the increase in phase angle (tan δ = G″/G′). Nevertheless, no change in primary structure was detected by Fourier transformation infrared (FT-IR) analysis. The results suggested that high intensity US was an effective means for KGM degradation without significant structural destruction. Graphical abstract: Highlights: Ultrasound (US) was effective for partial degradation of konjac glucomannan (KGM). US power and treatment period were major factors affecting the degradation. High-intensity US treatment caused dramatic reduction of KGM solution viscosity. US degradation of KGM followed the first-order polymer degradation kinetics.